Financial accountability in Nepal : a country assessment. - World Bank. (Washington, DC : World Bank, 2003)
Nepal has suffered from the lack of proper management of public expenditures, stagnant real revenues, large and inefficient parastatals and a weak financial sector. This study assesses the strengths and weaknesses of the budgeting, accounting, financial reporting and auditing systems.
Includes bibliographical references.
oif 10/03/15
Loan
Keywords: Finance, Public -- Nepal; Finance, Public -- Nepal -- Accounting